Clinical response to varying pollen exposure in allergic rhinitis in children in The Netherlands - Tameeris, Ellen; Bohnen, Arthur M.; Bindels, Patrick J. E.; Elshout, Gijs (BMC pediatrics, 2023)
Background Allergic rhinitis (AR) affects 10–15% of children. Symptoms in seasonal AR are influenced by pollen exposure. Pollen counts vary throughout the pollen season and therefore, symptom severity fluctuates. This study investigates the correlation between pollen concentration and symptom load in children with AR in The Netherlands. Methods A secondary analysis was performed in a study determining the most effective treatment for children with seasonal AR. Symptoms were measured during three months in 2013 and 2014 using a daily symptom diary. The pollen concentration was measured with a Hirst type volumetric spore trap sampler. A correlation coefficient was calculated for the correlation between the pollen concentration and the mean daily symptom score. The study protocol was approved by the medical ethical review committee of the Erasmus MC and is incorporated in the International Clinical Trials Registry Platform (EUCTR2012-001,591–11-NL). Results In 2014, the correlation coefficient for birch pollen concentration and symptom score was 0.423 ( p = 0.000). The correlation coefficient for grass pollen concentration and symptom score was 0.413 ( p = 0.000) and 0.655 ( p = 0.000) in 2013 and 2014, respectively. A delayed correlation between the birch pollen concentration and the symptom scores was seen up to two days after the pollen measurement (0.151, p = 0.031). For grass pollen this effect lasted up to three days after the pollen measurement (0.194, p = 0.000). Conclusion We found comparable correlations between symptom score and pollen concentration as found by EAACI. Birch and grass pollen have an elongated influence on symptom score of several days. This implies patients need to continue on demand medication longer after a measured pollen peak.